A new species of Eriocaulon (Eriocaulaceae) from Southern Western Ghats, Kerala, India. Issue 2 (3rd July 2017) - Naveen Kumar, V. V.; Sunil, C. N.; Remya Krishnan, C. R.; Sanilkumar, M. G.; Baiju, E. C.
Abstract: Eriocaulon periyarense, a new species from southern Western Ghats is described here. A detailed description, illustration, taxonomic note, phenology, ecology and distribution of the species are discussed.